The relationships of motor-evoked potentials to hand dexterity, motor function, and spasticity in chronic stroke patients: a transcranial magnetic stimulation study - AKYÜZ, GÜLSEREN DERYA; YAĞCI, İLKER; KARADAĞ SAYGI, NAİME EVRİM; GÜNDÜZ, OSMAN HAKAN (SPRINGER HEIDELBERG, 2016)
The standardization of patient evaluation and monitoring methods has a special importance in evaluating the effectiveness of therapeutic methods using drugs or rehabilitative techniques in stroke rehabilitation. The aim of this study was to investigate the relationships between clinical instruments and transcranial magnetic stimulation (TMS)-evoked neurophysiological parameters in stroke patients. This study included 22 chronic post-stroke patients who were clinically assessed using the Motricity Index (MI), finger-tapping test (FTT), Motor Activity Log (MAL) 28, Brunnstrom motor staging and Ashworth Scale (ASH). Motor-evoked potential (MEP) latency and amplitude, resting motor threshold (rMT) and central motor conduction time (CMCT) were measured with TMS. Shorter MEP-latency, shorter CMCT, higher motor-evoked potential amplitude, and diminished rMT exhibited significant correlations with clinical measures evaluating motor stage, dexterity, and daily life functionality. rMT exhibited a negative correlation with hand and lower extremity Brunnstrom stages (r = -0.64, r = -0.51, respectively), MI score (r = -0.48), FTT score (r = -0.69), and also with amount of use scale and quality of movement scale of MAL 28 scores (r = -0.61, r = -0.62, respectively). Higher MEP amplitude and diminished rMT showed positive correlations with reduced ASH score (r = -0.65, r = 0.44, respectively). The TMS-evoked neurophysiologic parameters including MEP latency, amplitude, rMT and CMCT generally have positive correlation with clinical measures which evaluate motor stage, dexterity and daily life functionality. Additionally, spasticity has also remarkable relationships with MEP amplitude and rMT. These results suggest that TMS-evoked neurophysiological parameters were useful measures for monitoring post-stroke patients.
Keywords: Dexterity; Motor-evoked potential; Neurorehabilitation; Spasticity; Transcranial magnetic stimulation; PROGNOSTIC VALUE; SUBCORTICAL STROKE; UPPER EXTREMITY; RECOVERY; POSTSTROKE; REHABILITATION; TRIALS; SCALES; OUTPUT; INDEX